MEMBENTUK KARAKTER MELALUI BIBLE CAMP: MENUMBUHKAN KEPEMIMPINAN DAN NILAI-NILAI MORAL DI KALANGAN MAHASISWA IAKN MANADO - Heydemans, Nency Aprilia; Salindeho, Veibe (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This research aims to explore the impact of Bible Camp as a means to form characters, strengthen leadership, and encourage moral values among students at the Manado, Manado’s Institut of Christian Religion (IAKN). Qualitative research methods are used, with dee interviews and participative observations as data collection instruments. The participants consisted of a student counseling pastoral study program that had followed the Bible Camp. The main theme in research findings is the positive influence of Bible Camp in developing student character, such as independence, perseverance, and courage. In addition, activities in Bible Camp also strengthen the giving skills through collaboration exercises, decision-making, and effective communication. Furthermore, Bible camp provides a container for students to understand and apply moral values, such as integrity, cooperation, and affection, ini everyday life. The impilications of this study indicate that Bible Camp can be an effective strategy in character education and leadership development in the University of Environment, especially among the students of IAKN Manado.